Comparative Analysis of Laravel and Symfony in PHP-Based Web Application Developmen - Putra, Fauzan Prasetyo Eka; Kusuma, Okky Firmansyah; Mursidi, Moh.; Hamzah, Amir (Brilliance: Research of Artificial Intelligence, 2025)
This research aims to compare two leading PHP frameworks, Laravel and Symfony, in the context of modern web application development. Using a Comparative Literature Study approach, this study analyses various relevant literature sources to evaluate the performance, ease of use, key features, security, as well as scalability and community support of each framework. Laravel is known for its simple and productive approach, making it popular among beginner to intermediate developers. Meanwhile, Symfony has a more complex and flexible architectural structure, which is often used in large-scale projects and enterprise systems. From the results of the study, it was found that Laravel is superior in terms of ease of use and the availability of extensive documentation, while Symfony shows more stable and flexible performance in large-scale applications. In terms of security, both frameworks provide protection features against common threats such as SQL Injection, CSRF, and XSS. Laravel has the upper hand in providing off-the-shelf solutions, while Symfony provides more advanced settings for experienced developers. Laravel's community support is also greater, making learning and development easier. This research provides an objective overview for developers in choosing a framework that suits the needs of the project, both from a technical and practical perspective.